Achalasia Subtypes Characteristics: Result of a Study in a Tertiary Hospital - Saba Alvand; Behnaz Aghaee; Zahra Momayez Sanat (Babol University of Medical Sciences, 2022)
Background: With the appearance of enhancing high-resolution manometry (HRM), realizing the difference of achalasia symptoms between classified groups by HRM is an outcome of interest in areas with remote access to this device. Methods: All patients newly diagnosed with achalasia from January 2019 to March 2020 were enrolled in the study. All the patients were diagnosed via HRM after undergoing endoscopy to rule out pseudo-achalasia, and grouped based on the Chicago classification criteria and answered a questionnaire assessing relevant symptoms. Results: We included 62 patients recently diagnosed with achalasia with a mean age of 53.66 in males (n=30), and 45.4 in females (n=32). Mean time of diagnosis was 24 months. Thirty-seven percent were in type I, 50% in type II, and 13% in type III. Dysphagia and weight loss were higher in type III, while all other relevant symptoms were higher in type II, none of which, however, was statistically significant. Weight loss was reversely associated with duration of symptoms (Spearman correlation= -0.3, P=0.01), and this reverse association was more prominent in females (Spearman correlation= -0.47, P=0.009), type III (Spearman correlation= -0.74, P=0.03), and in the first clinical stages (Spearman correlation= -0.55, P=0.04) in sub analysis. Conclusion: Type II is the most common type of achalasia in this study. Unlike HRM classification, clinical manifestations alone cannot be used to group patients into different types. However, significant weight loss of the newly diagnosed subjects can become an indicator of on-time diagnosis of the patients.